2017
DOI: 10.1186/s13104-017-2591-z
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic determinants of skilled birth attendant at delivery in rural southern Ghana

Abstract: BackgroundMaternal mortality is the subject of the United Nations’ fifth Millennium Development Goal, which is to reduce the maternal mortality ratio by three quarters from 1990 to 2015. The giant strides made by western countries in dropping of their maternal mortality ratio were due to the recognition given to skilled attendants at delivery. In Ghana, nine in ten mothers receive antenatal care from a health professional whereas only 59 and 68% of deliveries are assisted by skilled personnel in 2008 and 2010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
44
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 35 publications
28
44
2
Order By: Relevance
“…Determination of socioeconomic status as a proxy measure of a household's long term standard of living using calculated weights based on principal component analysis (PCA) [23] has been reported elsewhere [20,24].…”
Section: Variablesmentioning
confidence: 99%
“…Determination of socioeconomic status as a proxy measure of a household's long term standard of living using calculated weights based on principal component analysis (PCA) [23] has been reported elsewhere [20,24].…”
Section: Variablesmentioning
confidence: 99%
“…In both public health and social science literatures in diverse contexts, several studies have identified numerous factors contributing to home deliveries, including socio‐demographic, maternal, socio‐cultural, economic, health system, and geographical factors . Studies have shown that mothers' socio‐demographic characteristics, such as educational status, occupation, and residential area, influence their choice of place of delivery .…”
Section: Introductionmentioning
confidence: 99%
“…Other factors include socio‐cultural factors such as preferences for traditional birth attendants (TBAs), the influence of mothers‐in‐law, and beliefs that health facility delivery is a sign of weakness or marital infidelity . Economic factors such as low socio‐economic status and lack of health insurance have also been implicated. Health system factors including poor attitude of health care providers in Ghana, intimidation, unfriendliness and cultural insensitivity displayed by some health care providers in health care facilities in Ghana, poor quality of care alongside long distances to health care facilities in Ghana, and informal payments even in the context of user‐fee exemption for skilled delivery services also influence home delivery …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations